Histopathological identification of Coccidioidomycosis in animals at Dhaka Zoo (Bangladesh Veterinarian, 2014)
Dhaka Zoo with 2000 animals of 184 species and five million visitors a year is important from a public health point of view. This study was conducted to investigate coccidioidomycosis in captive animals at Dhaka Zoo. One hundred and two tissue samples were collected and preserved in 10% neutral buffered formalin at necropsy of 36 animals of 25 species. Twenty five animals were suffering from granulomatous diseases, of which ten were identified as coccidioidomycosis. Clinical history, nodular lesions at necropsy, granulomatous lesions on histopathology and characteristic spores on special staining confirmed coccidioidomycosis in six rhesus macaques (Macaca mulatta), one horse (Equus caballus), one common langur (Presbytis entellus), one beisa oryx (Oryx beisa beisa) and one reticulated python (Python molurus). It is suggested that coccidioidomycosis in captive animals threatens human and animal health. DOI: http://dx.doi.org/10.3329/bvet.v30i2.18255 Bangl. vet. 2013. Vol. 30, No. 2, 54-61